DIALEKTIKA SOCRATES: SEBUAH ALTERNATIF MENYIKAPI PRAHARA HOMO DIGITALIS - Daniel, Albertus; Hasibuan, Nelson (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Progress of the times brings digital technology. Most homo digitalis fail to respond to this. As a result, homo digitalis created a storm in the digital world. The widespread distribution, consumption of hoax news and brutality have even led to banality. This research uses a research method with library research, after being collected theoretically and arranged systematically, then the researcher uses the hermeneutic method. Socratic dialectics leads to balancing relationships, while at the same time responding to the tempest of homo digitalis. Of course, critical thinking will prevent the provocation of wrong information. By implementing Socratic dialectics, 1) Homo digitalis awakens from its deep sleep of the shackles of